2010
DOI: 10.1162/jocn.2010.21423
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Facilitation of Behavior in Monkeys: Effects of Stimulus Intensity

Abstract: Multisensory stimuli can improve performance, facilitating RTs on sensorimotor tasks. This benefit is referred to as the redundant signals effect (RSE) and can exceed predictions on the basis of probability summation, indicative of integrative processes. Although an RSE exceeding probability summation has been repeatedly observed in humans and nonprimate animals, there are scant and inconsistent data from nonhuman primates performing similar protocols. Rather, existing paradigms have instead focused on saccadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 92 publications
(135 reference statements)
7
20
1
Order By: Relevance
“…This observation fits with previous studies, which demonstrated an inverse relationship between the magnitude of the RTE for bisensory inputs and stimulus intensity (Corneil et al, 2002;Diederich and Colonius, 2004;Rach et al 2011). Interestingly, an inverse association between the magnitude of the RTE and the intensity of multisensory stimuli has been recently found also in monkeys (Cappe et al, 2010a). This observation, in addition to the present data, suggests that stimulus intensity influences integrative multisensory processing such that the RT facilitation effect to bisensory redundant targets is strongest when stimuli are low in intensity.…”
Section: The Bisensory Redundant Target Effect and Stimulus Intensitysupporting
confidence: 93%
“…This observation fits with previous studies, which demonstrated an inverse relationship between the magnitude of the RTE for bisensory inputs and stimulus intensity (Corneil et al, 2002;Diederich and Colonius, 2004;Rach et al 2011). Interestingly, an inverse association between the magnitude of the RTE and the intensity of multisensory stimuli has been recently found also in monkeys (Cappe et al, 2010a). This observation, in addition to the present data, suggests that stimulus intensity influences integrative multisensory processing such that the RT facilitation effect to bisensory redundant targets is strongest when stimuli are low in intensity.…”
Section: The Bisensory Redundant Target Effect and Stimulus Intensitysupporting
confidence: 93%
“…This detection task was comparable to previous studies conducted in human subjects (Giard and Peronnet, 1999; Molholm et al, 2002; Gori et al, 2011) and in macaques (Cappe et al, 2010). However, for the first time stimuli levels used with monkeys were based on individually determined perceptual thresholds in order to precisely determine the auditory versus visual stimuli intensities required to modify the multisensory gain in motor response latencies.…”
Section: Introductionsupporting
confidence: 89%
“…Mk-LI was 9 years old and Mk-JZ was 7 years old at the time of the onset of electrophysiological recordings. The monkeys Mk-LI and Mk-JZ are distinct from the two monkeys used in a previous study from this laboratory based on an earlier, less elaborate version of the psychophysical paradigm (Cappe et al, 2010), with some important differences as outlined in the discussion. The monkeys’ weight was monitored daily and both weighed around 8 kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of resolving this issue is highlighted by the mounting evidence in animal models documenting the prevalence of subadditive interactions that result in enhanced information content of responses (Bizley et al, 2007;Angelaki et al, 2009;). The topic of superadditive and subadditive interactions is likewise often intertwined with discussion of the applicability of the principle of inverse effectiveness, which would stipulate that unisensory stimulus conditions presented alone that are more effective in generating a neural response would more likely result in additive or even subadditive interactions when presented simultaneously as a multisensory pair Holmes, 2009;Cappe et al, 2010). Given that most ERP and fMRI studies of AV interactions involving rudimentary stimuli (i.e., tones/ noises and shapes/flashes) in humans have presented loud and highcontrast stimuli (i.e., suprathreshold stimuli), subadditive interactions would be expected to have been occurring (though as mentioned above were not statistically assessed) and are anticipated in the present study.…”
Section: Eeg Acquisition and Analysesmentioning
confidence: 99%